The Cohesion of the Error Management Culture and Risk Management Maturity in Healthcare - Buckė, Veronika; Ruželė, Darius; Ruževičius, Juozas; Buckus, Raimondas (Vilnius University Proceedings, 2023)
Errors and mistakes are an inevitable part of organisational life and certainly life in general. However, errors result in adverse events. The consequences of them influence the safety of the staff and the health of patients. The focus is on the following fundamental question regarding the scientific problem at the theoretical level: How the error management culture relates to risk management maturity in healthcare? The aim of this study is to theoretically ground the importance of the link between the error management culture and risk management maturity in the field of healthcare. Methods of the research are literature review and the critical analysis of the latest scientific articles on the issue. In conclusion, the error management culture leads to the lowered occurrence of adverse events, improved error reporting, improved prevention of medical errors, improved quality and safety of the clinical services, and proactivity with regard to errors.